A Template Editing Strategy to Create Interlayer‐Confined Active Species for Efficient and Durable Oxygen Evolution Reaction. Issue 2 (28th November 2022) - Liu, Depei; Yan, Yuandong; Li, Hu; Liu, Duanduan; Yang, Yandong; Li, Taozhu; Du, Yu; Yan, Shicheng; Yu, Tao; Zhou, Wei; Cui, Peixin; Zou, Zhigang
Abstract: Substantial overpotentials and insufficient and unstable active sites of oxygen evolution reaction (OER) electrocatalysts limit their efficiency and stability in OER‐related energy conversion and storage technologies. Here, a template editing strategy is proposed to graft highly active catalytic species onto highly conductive rigid frameworks to tackle this challenge. As a successful attempt, two types of NiO6 units of layered Ni BDC (BDC stands for 1, 4‐benzenedicarboxylic acid) metal organic frameworks are selectively edited by chemical etching‐assisted electroxidation to create layered γ‐NiOOH with intercalated Ni–O species. In such an interlayer‐confined intercalated architecture, the large interlayer space with high ion permeability offers an ideal reaction region to sufficiently expose the OER active sites comprising high‐density intercalated Ni–O species, which also suppresses the undesirable γ to β phase transformation, thus exhibiting efficient and durable OER activity. As a result, water oxidation can occur at an extremely low overpotential of 130 mV and affords 1000 h stability at 100 mA cm −2 . The strategy conceptually shows the possibility of achieving stable homogeneous‐like catalysis in heterogeneous catalysis. Abstract : An interlayer‐confined intercalated architecture is created by template editing, suppressing the undesirable γ to β phase transformation and exhibiting efficient and durable oxygen evolution reaction activity. As a result, water oxidation can occur at an extremely low overpotential of 130 mV and affords 1000 h stability at 100 mA cm −2 .